Update of Management of ANCA-Associated Vasculitis - Hoi San Tang (World Scientific Publishing, 2021)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is associated with significant morbidity and mortality. Management of AAV is divided into induction of remission and maintenance of remission. Management of AAV has evolved with the aim of improving treatment outcomes and minimizing treatment toxicities. In this article, we will review the latest evidence on the treatment of AAV.